Catalytic Innovations in the Aza-Michael Reaction: An Experimental Benchmarking Focused on Sustainable Approaches - Silvia Izquierdo; Carlos J. Durán-Valle; Pedro Cintas; Ignacio M. López-Coca (Molecules)
This study explores a series of eco-compatible, safe, inexpensive, and recyclable catalysts for the aza-Michael reaction, an essential transformation for constructing C-N bonds. In particular, we focus on hydrothermal carbons (HCB and HCC) prepared from chestnut cupule waste under mild, aqueous conditions, offering a sustainable alternative to traditional pyrolytic methods. These carbonaceous solids, thoroughly characterized by physicochemical techniques, exhibit notable catalytic activity, completing aza-Michael reactions in as little as 5–30 min for various model substrates. Their performance was benchmarked against Montmorillonite K10, [Cho][Pro] ionic liquid, and K10+[Cho][Pro], with the latter combination and [Cho][Pro] alone giving the fastest conversions. For example, the reaction of benzylamine with acrylonitrile reached complete conversion (typically 95% yield) in five minutes using [Cho][Pro], K10+[Cho][Pro], or likewise with HCB and HCC. Although the reactions catalyzed by hydrothermal carbons did not outperform in general those using K10-[Cho][Pro] or [Cho][Pro], they proceeded rapidly and afforded good to excellent yields. Furthermore, the HCC catalyst demonstrated excellent recyclability, maintaining its activity and yield over at least five cycles. These findings underscore the potential of hydrothermal carbons as efficient green heterogeneous catalysts, combining high surface area, porosity, and reusability with strong catalytic performance and scalability, in alignment with the principles of the circular economy.